2018
DOI: 10.5194/acp-18-4519-2018
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation of nitric acid hydrates in polar stratospheric clouds by meteoric material

Abstract: Abstract. Heterogeneous nucleation of crystalline nitric acid hydrates in polar stratospheric clouds (PSCs) enhances ozone depletion. However, the identity and mode of action of the particles responsible for nucleation remains unknown. It has been suggested that meteoric material may trigger nucleation of nitric acid trihydrate (NAT, or other nitric acid phases), but this has never been quantitatively demonstrated in the laboratory. Meteoric material is present in two forms in the stratosphere: smoke that resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(65 citation statements)
references
References 59 publications
(99 reference statements)
4
36
1
Order By: Relevance
“…Based largely on these arguments, meteoritic material emerged as a suitable trigger for the formation of low number density NAT or synoptic-scale ice clouds in the stratosphere. This was recently confirmed by James et al (2018), who showed that proxies for both meteoritic materials, smoke particles (amorphous silica analogs: fumed silica and fused quartz) and meteoritic fragments (ground meteorite analogs), have a capacity to nucleate TRITSCHER ET AL. HNO 3 hydrates.…”
Section: The Possible Origin Of Heterogeneous Nat Nucleimentioning
confidence: 72%
“…Based largely on these arguments, meteoritic material emerged as a suitable trigger for the formation of low number density NAT or synoptic-scale ice clouds in the stratosphere. This was recently confirmed by James et al (2018), who showed that proxies for both meteoritic materials, smoke particles (amorphous silica analogs: fumed silica and fused quartz) and meteoritic fragments (ground meteorite analogs), have a capacity to nucleate TRITSCHER ET AL. HNO 3 hydrates.…”
Section: The Possible Origin Of Heterogeneous Nat Nucleimentioning
confidence: 72%
“…The HNO 3 dataset has a vertical resolution of approximately 3-4 km, while the H 2 O and O 3 datasets have a vertical resolution of 2.5 to 3 km. The accuracy of the MLS measurements is 1-2 ppbv for HNO 3 , 4 %-7 % for H 2 O (Read et al, 2007;Lambert et al, 2007) and 8 % for stratospheric O 3 (Jiang et al, 2007). Detailed information and a precise description of the dataset can be found in Livesey et al (2018).…”
Section: Mls Observationsmentioning
confidence: 99%
“…MSPs are formed by the ablation of meteors or interplanetary dust particles in the upper atmosphere, as was originally hypothesized by Rosinski and Snow (1961). The ablation process causes meteoric vapours to be released, mostly at altitudes around 90 km in the mesopause region, during entry into the atmosphere at high velocities (Kalashnikova et al, 2000;Plane, 2003). Hereafter, such vapours undergo gas phase reactions with atmospheric gases and ions and ultimately recondense, leading to tiny aerosol particles (Plane, Figure 1.…”
Section: Introductionmentioning
confidence: 94%